Autobiographical memory in semantic dementia: Implications for theories of limbic-neocortical interaction in remote memory - McKinnon, Margaret C. (2006)
We examined autobiographical memory performance in two patients with semantic dementia using a novel measure, the Autobiographical Interview [Levine, Svoboda, Hay, Winocur, & Moscovitch (2002). Aging and autobiographical memory: Dissociating episodic from semantic retrieval. Psychology and Aging, 17, 677–689], that is capable of dissociating episodic and personal semantic recall under varying levels of retrieval support. Earlier reports indicated that patients with semantic dementia demonstrate autobiographical episodic memory loss following a “reverse gradient” by which recent memories are preserved relative to remote memories. We found limited evidence for this pattern at conditions of low retrieval support. When structured probing was provided, patients’ autobiographical memory performance was similar to that of controls. Retesting of one patient after 1 year indicated that retrieval support was insufficient to bolster performance following progressive prefrontal volume loss, as documented with quantified structural neuroimaging. These findings are discussed in relation to theories of limbic-neocortical interaction in autobiographical memory.